Partisipasi Masyarakat Desa Sembungan Dalam Konservasi Alam - Mohamad Burchanuddin; Didin Syarifuddin (Balimau: Jurnal Budaya Lokal, 2026)
This study aims to comprehensively examine community participation in environmental conservation in Sembungan Village, Kejajar District, Wonosobo Regency, the highest village on Java Island, which possesses significant ecotourism potential while simultaneously facing environmental degradation risks resulting from economic and tourism-related activities. The study focuses on identifying forms of community participation in environmental conservation and analyzing the driving and inhibiting factors influencing local engagement in community-based conservation practices. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and documentation. The research involved eight purposively selected key informants, including the village head, community leaders, tourism managers, farmers, and housewives. The findings reveal that the people of Sembungan Village actively participate in conservation initiatives, including mountain reforestation, domestic waste management, spring water protection, and the strengthening of collective action grounded in local wisdom and communal values. High ecological awareness, economic dependence on environmental sustainability, and strong village institutional support emerged as major driving factors of participation. Conversely, limited technical knowledge, inadequate financial and external support, and relatively low youth involvement constitute major barriers to sustainable participation. These findings underscore the importance of empowering local communities through culturally grounded environmental education, institutional capacity strengthening, and multi-stakeholder partnerships to foster inclusive, adaptive, and sustainable environmental conservation.